Els Quadres del primer catalanisme polític, 1882-1900 / Joaquim Coll i Amargós, Jordi Llorens i Vila - Llorens, Jordi (1958-); Coll i Amargós, Joaquim (Biblioteca Abat Oliba ; 227)
Bibliografía: p. 351-358